Corporate risk management: a case study of SAA - Ramaremisa, Ndivhuwo (My University, 2014)
Corporate Risk management has become very important for firms who are exposed to markets risks. A firm that manages the market risks it is exposed to efficiently can ensure it remains solvent in times of extreme market volatility. This paper looks at the hedging activities of South African Airways over a 10 year period where the airline experienced significant losses due to volatility in the Rand Exchange Rate and Crude Oil prices.
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2014.
Keywords: South African Airways; Corporate risk management; Hedging; Derivatives; Hedging policy; Currency risk; Commodity risk